1995
DOI: 10.1089/clm.1995.13.315
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Argon Laser and Conventional Light-Cured Composites

Abstract: This study was conducted to compare and evaluate the diametral tensile strengths of four current commercial composite resins cured with an argon laser versus a conventional (conv.) visible light. The argon laser (HGM Model 8) at 231, 280, and 450 mW, 5 mm beam size, and 10 sec exposure and a conventional visible light unit (the Max) at 20 and 40 sec exposure were used to polymerize samples of composite resins: AelitefU, Charisma, Silux Plus, and TPH. The samples were stored in light proof containers for 24 hr … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Studies continue to support the ability of the argon laser to cure composite fast and effectively. 11,42,43,44 Vergas et al 11 reported adequately polymerized composite resin in 30% to 50% less time. Christensen and Christensen 44 reported efficient polymerization in 10 seconds or less for five different resins.…”
Section: Micro Hardnessmentioning
confidence: 99%
“…Studies continue to support the ability of the argon laser to cure composite fast and effectively. 11,42,43,44 Vergas et al 11 reported adequately polymerized composite resin in 30% to 50% less time. Christensen and Christensen 44 reported efficient polymerization in 10 seconds or less for five different resins.…”
Section: Micro Hardnessmentioning
confidence: 99%